2021
DOI: 10.21608/aja.2021.205206
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Mediating Role of Green Organizational Culture on the Relation between Human Resources Green Competencies and Organizational Environmental Performance in Major Palestinian Governmental Hospitals in the Gaza Strip

Abstract: This study aims at shedding light on the reality of human resource green competencies in Palestinian government hospitals in the Gaza Strip, clarifying the role of those competencies in improving organizational environmental performance. Furthermore, it clarifies the impact of green organizational culture on the relation between human resource green competencies and organizational environmental performance. The descriptive analytical approach was adopted. In addition, a questionnaire was designed to collect da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In additional, there is little research on GMOC compared to previous research literature, so this will be one of the gaps to be examined in this paper. Meanwhile, GMOC has been researched in the context of companies (Abou-AL-Ross & Abu Mahadi, 2021;Tahir et al, 2019), Nevertheless, in contrast to the corporate sector, GMOC research has paid little attention to educational institutions. So that, there exist gaps in GMOC in the context of sustainable higher education institutions, which is an emerging area of research for future development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In additional, there is little research on GMOC compared to previous research literature, so this will be one of the gaps to be examined in this paper. Meanwhile, GMOC has been researched in the context of companies (Abou-AL-Ross & Abu Mahadi, 2021;Tahir et al, 2019), Nevertheless, in contrast to the corporate sector, GMOC research has paid little attention to educational institutions. So that, there exist gaps in GMOC in the context of sustainable higher education institutions, which is an emerging area of research for future development.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the least researched with respect to GMOC while still expanding the research on developing countries (Al-Swidi et al, 2021). Meanwhile, researchers have suggested that GMOC practices play a significant role in developing, motivating, and involving employees in improving environmental management (Abou-AL-Ross & Abu Mahadi, 2021).…”
Section: Introductionmentioning
confidence: 99%